Deletion of exons 4-10 in the IKBKG gene causes incontinentia pigmenti in a Vietnamese child - Nguyen, Khanh Linh; Le, Tran Thanh Ha; Nguyen, Thuy Duong; Nguyen, Hai Ha (Vietnam Journal of Biotechnology, 2025)
Incontinentia pigmenti (IP) is an X-linked dominant genetic disorder caused by mutations in the inhibitor of kappa B kinase gamma (IKBKG) gene. Common symptoms of this disease include skin manifestations such as blisters, warty lesions, and hyperpigmentation, as well as skin atrophy and abnormalities in nails, hair, teeth, and the central nervous system. This study aims to identify the pathogenic mutation of a Vietnamese female infant suspected of having IP conditions. Using multiple genotyping methods, including whole-exome sequencing (WES), multiplex ligation-dependent probe amplification (MLPA), and polymerase chain reaction (PCR), we identified that the patient carried a heterozygous deletion encompassing exons 4-10 of the IKBKG gene. This mutation was reported as the most prevalent genetic cause in IP patients worldwide. The patient’s mutation was de novo, as her parents were negative for it. This is the first case of IP reported with the identified genetic etiology in Vietnam and provides valuable information to the Vietnamese population’s genetic database of ectodermal dysplastic disorders. Given the high prevalence of the exons 4-10 deletion in the IKBKG gene among IP patients worldwide, we recommend using a low-cost PCR to detect this deletion as the initial screening test for pathogenic mutations in Vietnamese IP patients, followed by sequencing methods if the PCR test is negative.